Distributed secondary control for power allocation and voltage restoration in islanded DC microgrids - Guo, Fanghong (2020)
This paper presents a distributed secondary control scheme for accurate power allocation and voltage restoration in islanded dc microgrids. Conventionally the droop control function is employed in the primary control layer to realize power sharing among the distributed generators (DGs) in a decentralized fashion. However, the dc bus voltage may deviate from its nominal value due to different load profiles. In order to restore the dc bus voltage to its nominal value while maintaining the power sharing accuracy, a distributed control scheme is proposed in the secondary control layer. By using limited information of dc bus voltage and the secondary control inputs of their neighboring controllers, a distributed secondary control input can be designed and then sent to its corresponding primary controller. Besides, compared to most existing methods, no global information is required and only dc bus voltage feedback is needed. In addition, by employing the idea of pinning control, our proposed secondary control can be further simplified by only sending the dc bus voltage to one DG. An islanded dc microgrid test system is built in the MATLAB Simulink environment to validate our proposed method. An experimental prototype consisting of two DGs is designed to demonstrate the newly proposed approach and verify the obtained theoretical results.